Similar enhancement of BK(Ca) channel function despite different aerobic exercise frequency in aging cerebrovascular myocytes - Li, N; Liu, B; Xiang, S; Shi, L (Physiological research, 2016)
Aerobic exercise showed beneficial influence on cardiovascular systems in aging, and mechanisms underlying vascular adaption remain unclear. Large-conductance Ca(2+)-activated K(+) (BK(Ca)) channels play critical roles in regulating cellular excitability and vascular tone. This study determined the effects of aerobic exercise on aging-associated functional changes in BK(Ca) channels in cerebrovascular myocytes, Male Wistar rats aged 20-22 months were randomly assigned to sedentary (O-SED), low training frequency (O-EXL), and high training frequency group (O-EXH). Young rats were used as control. Compared to young rats, whole-cell BK(Ca) current was decreased, and amplitude of spontaneous transient outward currents were reduced. The open probability and Ca(2+)/voltage sensitivity of single BK(Ca) channel were declined in O-SED, accompanied with a reduction of tamoxifen-induced BK(Ca) activation; the mean open time of BK(Ca) channels was shortened whereas close time was prolonged. Aerobic exercise training markedly alleviated the aging-associated decline independent of training frequency. Exercise three times rather than five times weekly may be a time and cost-saving training volume required to offer beneficial effects to offset the functional declines of BK(Ca) during aging.
Keywords: potkani Wistar; Physical Conditioning, Animal; Middle Cerebral Artery; zvířata; Male; Muscle Cells; Aging; arteria cerebri media; Animals; mužské pohlaví; tělesná hmotnost; Rats, Wistar; Blood Pressure; Body Weight; krevní tlak; stárnutí; svalové buňky; Large-Conductance Calcium-Activated Potassium Channels; kondiční příprava zvířat; vápníkem aktivované draslíkové kanály s vysokou vodivostí